Macrophage Phagocytosis and Allergen Avoidance in Children With Asthma - Kulkarni, Neeta; Kantar, Ahmad; Costella, Silvia; Ragazzo, Vincenzo; Piacentini, Giorgio; Boner, Attilio; O'Callaghan, Christopher (Frontiers in Pediatrics, 2018)
Background and objective: Airway macrophages perform the crucial functions of presenting antigens, clearing pathogens and apoptotic cells. Macrophage phagocytosis is increased in adults with mild asthma and allergen exposure is known to activate macrophages. However, it is not clear whether the mechanism behind this is due to a primary defect or environmental factors such as allergen or lipopolysaccaride (LPS) exposure. Our aim was to assess the phagocytic function of airway macrophages in children with mild to moderate asthma after residence in a low allergen\LPS environment at high altitude. Methods: Sputum induction was performed in children with asthma at baseline and after residence for a 3 weeks’ period at a high-altitude asthma center that has very low ambient allergen levels. The markers of eosinophilic inflammation (including percentage of macrophage cytoplasm with red hue) and phagocytosis of fluorescein isothiocyanate-labeled, heat-killed Staphylococcus aureus by airway macrophages was analyzed. Internalized bacteria were quantified using confocal microscopy. Results: The median bacterial count [mean (standard deviation)] per macrophage was significantly lower [39.55 (4.51) vs. 73.26 (39.42) (p = 0.006)] after residence at high altitude. No association was observed between markers of eosinophilic inflammation and bacterial phagocytosis. Conclusions: The results suggest that the mechanism behind the enhanced phagocytosis of bacteria in childhood asthma may be secondary to allergen or possibly LPS exposure. Key words: Macrophages, phagocytosis, asthma, children, allergen avoidance